PERAN MAHASISWA PRODI DKV UPN VETERAN JAWA TIMUR DALAM PENYUSUNAN COMPANY PROFILE SDN KALIASIN I SURABAYA STUDI KASUS PROGRAM KKN - hasbiyahpuansyafa (ARDVIS, 2025)
Community Service Program (KKN) is a form of community service carried out by students. Through this activity, students are expected to be able to apply the knowledge gained in lectures to make a real contribution to the community. In this KKN program, students from the Visual Communication Design (DKV) Study Program at the National Development University "Veteran" East Java carried out community service at SDN Kaliasin 1 Surabaya. The purpose of the KKN Community Service Program for Visual Communication Design (DKV) UPN "Veteran" East Java Students is to assist SDN Kaliasin I Surabaya in compiling a company profile that can improve its image and introduce the school to the wider community. This activity is carried out by involving students in the creative process of creating graphic designs, collecting data, and writing relevant and informative content. Through this program, students can apply the knowledge gained during lectures, such as graphic design, visual communication, and branding. In addition, the results of the preparation of this company profile are expected to provide a positive contribution to SDN Kaliasin I in building a reputation and expanding the reach of information about the school. This activity also provides a platform for students to contribute directly to society and make a real impact.